Targeting cancer cell metabolism with mitochondria-immobilized phosphorescent cyclometalated iridium(iii) complexes - Jianjun Cao; Cai‐Ping Tan; Mu‐He Chen; Na Wu; Deyang Yao; Xingguo Liu; Liang‐Nian Ji; Zong‐Wan Mao (2016)
We report a rational design and mechanism studies of mitochondria-immobilized iridium(iii) complexes that can kill cancer cells by targeting mitochondrial metabolism.